Stronger legs means higher jumps? Exploring the role of maximal isometric strength on vertical jump performance in competitive female handball and basketball players - García-Sánchez, C.; Nieto-Acevedo, R.; Romero-Moraleda, B.; Lominchar-Ramos, J. M.; Jiménez-Ormeño, E.; Alonso-Aubín, D. A.; Soriano, M. A. (International Journal of Sports Physiology and Performance, 2026)
Objective: The aim of this study was to (1) explore differences in countermovement jump (CMJ) force-time metrics between stronger and weaker female handball and basketball players, (2) examine relationships between isometric midthigh pull (IMTP) peak force and CMJ metrics, and (3) produce reference values for CMJ and IMTP metrics.